Analysis of Human Reliability in Fever Clinics during the Epidemic Based on the DEMATEL Method - Ange Lin; Xiongfeng Chen (Journal of Electrical and Computer Engineering)
Objective. To explore the method and process of human reliability analysis in epidemic prevention and control system in the complex environment of fever clinics. Methods. Based on the actual situation in the fever clinic of a level A tertiary hospital in Wenzhou, factors that affect clinical safety are sorted out. The Delphi method is used when evaluating the interrelationship among the contributing factors, and then, the DEMATEL method is used to further sort it out to build an impact model. Finally, the data of the experimental model are analyzed, and the impact of factors on human reliability is summarized. Results. Through the data analysis of 23 factors in the fever clinic of the hospital, the impact, prominence, and relation of each factor are confirmed. It is concluded that layout design, disinfection, and isolation setting and on-the-job training are the core factors impacting the operation of the fever clinic. Conclusion. Conducting a human factor reliability analysis with the help of the DEMATEL method can quantitatively describe the influence and interrelationship of human factors in epidemic prevention and control system and effectively promote the safety enhancement of fever clinics.